All-solid-state battery including expandable negative electrode layer and method of operating same

By designing the particle and particle holes that can form alloys with lithium in the negative electrode layer of a all -solid -state battery, and use the creep phenomenon to accommodate lithium metal, it solves the problem of being difficult to effectively accommodate the existing battery in the charging process. High -energy density and safety.

CN119340492APending Publication Date: 2025-01-21HYUNDAI MOTOR CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410096944.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-19
Filing Date
2024-01-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing all-solid-state batteries are difficult to effectively accommodate lithium metal during charging, resulting in insufficient energy density and safety hazards.

Method used

A negative electrode layer including particles and inter-particle pores is designed. The particles can form an alloy with lithium. The lithium metal is accommodated in the inter-particle pores through creep phenomenon during charging and increases the size of the inter-particle pores through alloying.

Benefits of technology

The ability to accommodate large amounts of lithium metal during charging is achieved, improving the energy density and safety of the battery while extending the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340492A_ABST
    Figure CN119340492A_ABST
Patent Text Reader

Abstract

An all-solid-state battery including a negative electrode layer that expands during charging and contains lithium metal and a method of operating the same are provided. The all-solid-state battery comprises a negative electrode current collector, a negative electrode layer arranged on the negative electrode current collector, a solid electrolyte layer arranged on the negative electrode layer, a positive electrode active material layer arranged on the solid electrolyte layer and a positive electrode current collector arranged on the positive electrode active material layer. The negative electrode layer includes particles including a metal capable of alloying with lithium, and inter-particle pores.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an all-solid-state battery including a negative electrode layer that expands and accommodates lithium metal during charging, and a method of operating the same. Background Art

[0002] All-solid-state batteries are composed of solid-state components, so the risk of fire and explosion is generally less than that of lithium-ion batteries using flammable organic solvents as electrolytes. In addition, in all-solid-state batteries, there may be no safety issues even if lithium metal is used as the negative electrode active material because the mechanical strength of the solid electrolyte is high. In addition, when an anodeless structure is used in which lithium is used as the negative electrode active material but lithium is not included during battery assembly, and when lithium supplied by the positive electrode active material is deposited on the negative electrode current collector, the energy density can be further increased. Summary of the invention

[0003] An object of the present invention is to provide an all-solid-state battery comprising a negative electrode layer capable of accommodating a large amount of lithium metal during charging.

[0004] The purpose of the present invention is not limited to the above content. The purpose of the present invention can be clearly understood through the following description and can be achieved through the methods described in the claims and their combinations.

[0005] An embodiment of the present invention provides an all-solid-state battery, which includes a negative electrode current collector, a negative electrode layer disposed on the negative electrode current collector, a solid electrolyte layer disposed on the negative electrode layer, a positive electrode active material layer disposed on the solid electrolyte layer, and a positive electrode current collector disposed on the positive electrode active material layer, wherein the negative electrode layer may include particles and inter-particle pores, and the particles include a metal that can form an alloy with lithium.

[0006] The metal may include one or more of magnesium (Mg), silver (Ag), zinc (Zn), bismuth (Bi), tin (Sn), and combinations thereof.

[0007] The average particle size (D50) of the particles may be 300 nm to 700 nm.

[0008] In the negative electrode layer, the particles can maintain a spherical or ellipsoidal shape.

[0009] The negative electrode layer may consist of particles only.

[0010] The particles may also include alloys of metals and lithium.

[0011] During charging of all-solid-state batteries, lithium metal can be accommodated in the inter-particle pores.

[0012] During charging of all-solid-state batteries, alloying between particles and lithium can occur.

[0013] During charging of the all-solid-state battery, lithium metal may be deposited on the surface of the particles, which may increase the distance between the particles, thus enlarging the inter-particle pores and accommodating the lithium metal in the inter-particle pores.

[0014] The negative electrode layer may satisfy the following Formula 1.

[0015] [Formula 1]

[0016] 2≤T 2 / T 1 ≤5.9

[0017] Here, T 1 It can be the thickness of the negative electrode layer when the all-solid-state battery is fully discharged, T 2 It can be the thickness of the negative electrode layer when the entire solid-state battery is fully charged.

[0018] The peak intensities at 2θ=32°±0.5°, 34°±0.5°, and 37°±0.5° appearing in the X-ray diffraction analysis results of the negative electrode layer may decrease as charge and discharge proceed.

[0019] The peak intensity at 2θ=36°±0.5° appearing in the X-ray diffraction analysis result of the negative electrode layer may increase as charge and discharge proceed. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and other features of the present invention will now be described in detail with reference to certain exemplary embodiments of the invention shown in the accompanying drawings, which are given below by way of illustration only and therefore do not limit the present invention, and in which:

[0021] Figure 1 A schematic diagram showing an example all-solid-state battery according to the present invention;

[0022] Figure 2 A schematic diagram showing an example all-solid-state battery according to the present invention when fully charged;

[0023] Figure 3A shows the internal structure of an example negative electrode layer according to the present invention;

[0024] Figure 3B Displays the charging period Figure 3A The internal structure of the negative electrode layer;

[0025] Figure 3C When fully charged Figure 3A The internal structure of the negative electrode layer;

[0026] Figure 4Ais an example transmission electron microscope (TEM) image showing magnesium powder according to the present invention;

[0027] Figure 4B is an example TEM image showing a cross-sectional view of a solid electrolyte layer and a negative electrode layer of a half-cell according to the present invention;

[0028] Figure 5A The half-cell is shown at 1 mAh / cm 2 Example scanning electron microscope (SEM) image of a cross-sectional view of the negative electrode layer during charge;

[0029] Figure 5B The half-cell is shown at 2 mAh / cm 2 Example SEM image of a cross-sectional view of the negative electrode layer during capacity charging;

[0030] Figure 5C The half-cell is shown to be 4 mAh / cm 2 Example SEM image of a cross-sectional view of the negative electrode layer during capacity charging;

[0031] Figure 5D Energy dispersive spectroscopy (EDS) analysis and Figure 5A Example results for the same cross-section in;

[0032] Figure 5E The use of energy dispersive spectroscopy to analyze Figure 5B Example results for the same cross-section in;

[0033] Fig. 5F The use of energy dispersive spectroscopy to analyze Figure 5C Example results for the same cross-section in;

[0034] Figure 6 An example TEM image showing particles removed from a charged negative electrode layer after 10 charge / discharge cycles of a half-cell according to Example 1;

[0035] Figure 7 shows an example result of X-ray diffraction analysis of the negative electrode layer of the half-cell according to Example 1;

[0036] Figure 8 Shown at 0.5mA / cm 2 and 1mAh / cm 2 Example results of measuring the Coulombic efficiency of the half-cells according to Example 1 and the comparative example during charge / discharge under the conditions of;

[0037] Fig. 9 Shown at 0.5mA / cm 2 and 2mAh / cm2 Example results of measuring the coulombic efficiency of the half-cells according to Example 1 and the comparative example during charge / discharge under the conditions of;

[0038] Fig.10 Shown at 0.5mA / cm 2 and 2mAh / cm 2 Example voltage distribution in the first cycle and the second cycle when the half-cell according to Example 1 is charged / discharged under the conditions of;

[0039] Fig.11 The cycle capacity and cycle Coulombic efficiency of the full battery according to Example 2 are shown. DETAILED DESCRIPTION

[0040] The above and other purposes, features and advantages of the present invention will be more clearly understood by the following preferred embodiments in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed herein and can be modified into different forms. These embodiments are provided in order to thoroughly explain the present invention and fully convey the spirit of the present invention to those skilled in the art.

[0041] In the accompanying drawings, the same reference numerals will refer to the same or similar elements. Unless otherwise stated, all numerals, values ​​and / or expressions (representation) used in this article indicating the amount of components, reaction conditions, polymer compositions and mixtures should be regarded as approximate values, including various uncertainties affecting the measurement that occur inherently when obtaining these values, and therefore should be understood in all cases as modified by the term "about". In addition, unless otherwise stated, when a numerical range is disclosed in this specification, the range is continuous and includes all values ​​from the minimum value of the range to its maximum value. In addition, when such a range involves integer values, all integers including from the minimum value to the maximum value are included, unless otherwise stated.

[0042] Figure 1 Referring to this, the all-solid-state battery may be configured by stacking a negative electrode collector 10 , a negative electrode layer 20 , a solid electrolyte layer 30 , a positive electrode active material layer 40 , and a positive electrode collector 50 . Figure 1 A fully discharged all-solid-state battery is shown. Here, fully discharged may refer to a state of charge (SOC) of zero.

[0043] Figure 2FIG. 2 shows a fully charged all-solid-state battery according to the present invention. Here, fully charged may refer to a SOC of 100. The lithium ions (Li 2+) released from the positive electrode active material layer 40 are + ) moves to the negative electrode layer 20 through the solid electrolyte layer 30. Lithium ions (Li + ) is reduced at the interface between the solid electrolyte layer 30 and the negative electrode layer 20″ and is accommodated in the negative electrode layer 20 in the form of lithium metal. Since the negative electrode layer 20 according to the present invention expands during charging and accommodates lithium metal, a large amount of lithium metal can be stored compared to a conventional battery, which will be described later.

[0044] The negative electrode current collector 10 may be a plate-type substrate having conductivity. Specifically, the negative electrode current collector 10 may be in the form of a sheet, a film, or a foil.

[0045] The negative electrode current collector 10 may include a substance that does not react with lithium. Specifically, the negative electrode current collector 10 may include one or more of nickel (Ni), copper (Cu), stainless steel, and a combination thereof.

[0046] Figure 3A 2 is a reference diagram showing the internal structure of the negative electrode layer 20 according to the present invention. Specifically, Figure 3A The negative electrode layer 20 of the all-solid-state battery according to the present invention is shown before charging or after it is fully discharged.

[0047] The negative electrode layer 20 may include particles 21 and inter-particle pores 22. Each inter-particle pore 22 may be a space between any one particle 21 and another particle 21 adjacent thereto.

[0048] The particles 21 may include a metal capable of forming an alloy with lithium. The metal may include one or more of magnesium (Mg), silver (Ag), zinc (Zn), bismuth (Bi), tin (Sn), and combinations thereof.

[0049] The average particle size (D50) of the particles 21 can be 300nm-700nm. The average particle size (D50) of the particles 21 is a factor that can determine the size of the inter-particle pores 22. When D50 falls within the above numerical range, inter-particle pores 22 having the desired size of the present invention can be formed. The average particle size (D50) can be measured using a commercially available laser diffraction scattering-type particle size distribution analyzer, such as a Microtrac particle size distribution analyzer. Alternatively, 200 particles can be arbitrarily extracted from an electron micrograph and their average particle size can be calculated.

[0050] In some cases, the particles 21 may maintain a spherical or elliptical shape in the negative electrode layer 20. Therefore, when the all-solid-state battery is repeatedly charged and discharged, problems such as disappearance of the inter-particle pores 22 due to aggregation of the particles 21 are less likely to occur.

[0051] The negative electrode layer 20 may be composed only of particles 21. Specifically, in some cases, the negative electrode layer 20 may not include an active material capable of inserting and extracting lithium ions, such as a silicon-based negative electrode active material, a carbon-based negative electrode active material, etc. In addition, the negative electrode layer 20 may not include an electrolyte having lithium ion conductivity, such as a solid electrolyte, a polymer electrolyte, etc. In addition, the negative electrode layer 20 may not include a binder that allows the particles 21 to be bonded to each other.

[0052] The particles 21 may also include an alloy of metal and lithium. The particles 21 may include a metal, an alloy of metal and lithium, or a metal and an alloy. This will be described in more detail by the charging mechanism of the all-solid-state battery according to the present invention.

[0053] Figure 3B The internal structure of the negative electrode layer 20' during charging of the all-solid-state battery according to the present invention is shown. Figure 3C The internal structure of the negative electrode layer 20" when the all-solid-state battery according to the present invention is fully charged is shown.

[0054] When the all-solid-state battery starts charging, lithium ions (Li +) moves to the negative electrode layer 20 through the solid electrolyte layer 30. Since the electrons conduct through the particles 21 in the negative electrode layer 20 more efficiently than lithium ions (Li + ) conducts much faster through the solid electrolyte layer 30, so most lithium ions (Li + ) is reduced and deposited on the interface between the solid electrolyte layer 30 and the negative electrode layer 20.

[0055] Reference Figure 3B , since the alloying between the metal and lithium used for the particles 21 is relatively slow, an alloy of the metal and lithium may not be formed in the initial stage of charging. The lithium metal L can grow using the lithium metal deposited on the interface between the solid electrolyte layer 30 and the negative electrode layer 20 as a seed, and the lithium metal L is accommodated in the inter-particle pores 22 by the creep phenomenon. Therefore, the interface between the solid electrolyte layer 30 and the negative electrode layer 20' may not be separated by the growing lithium metal L, and lithium dendrites may not grow. The creep phenomenon refers to the deformation of a certain material over time when it is subjected to a stress equal to or less than the yield strength. The present invention stores lithium by Coble creep. Since Coble creep occurs at low temperatures, it is beneficial to the low temperature operation of the all-solid-state battery. For example, the all-solid-state battery according to the present invention can be operated at about 25°C-45°C to utilize this phenomenon. In addition, the all-solid-state battery can be charged while applying a predetermined pressure to it, so that the creep phenomenon occurs more effectively. For example, an all-solid-state battery may be operated in a state where a pressure of about 1 MPa to 30 MPa is applied in a stacking direction of the all-solid-state battery.

[0056] Reference Figure 3C As the all-solid-state battery continues to be charged, particles 21'' composed of an alloy of metal and lithium are formed. As a result, lithium metal is deposited on the surface of the particles 21'', thereby widening the gaps between the particles 21'' and expanding the inter-particle pores. Specifically, an expanded negative electrode layer 20'' is formed, and the lithium metal L is again accommodated in the expanded inter-particle pores.

[0057] The negative electrode layer 20, 20" containing lithium metal according to the present invention and according to the above-mentioned mechanism may satisfy the following Formula 1.

[0058] [Formula 1]

[0059] 2≤T 2 / T 1 ≤5.9

[0060] Here, if Figure 1 As shown, T 1It can be the thickness of the negative electrode layer 20 when the all-solid-state battery is fully discharged, such as Figure 2 As shown, T 2 It can be the thickness of the negative electrode layer 20" when the all-solid-state battery is fully charged. Therefore, full discharge can refer to a state of charge (SOC) of 0, and full charge can refer to an SOC of 100. In addition, when the charge capacity of the all-solid-state battery is 4 mAh / cm 2 When the charge capacity is less than 0.1 mAh / cm, Equation 1 can be applied. The lower limit of the charge capacity is not particularly limited and can be 0.1 mAh / cm 2 Above, 0.5mAh / cm 2 Above or 1mAh / cm 2 above.

[0061] The negative electrode layer 20 according to the present invention satisfying Formula 1 can accommodate a large amount of lithium compared to conventional batteries.

[0062] Here, T 1 There is no particular limitation, but it can be 1 μm to 10 μm, and T 2 can have appropriate values, depending on T 1 And the above formula 1.

[0063] The solid electrolyte layer 30 may be provided between the positive electrode active material layer 40 and the negative electrode layer 20 , and may include a solid electrolyte having lithium ion conductivity.

[0064] The solid electrolyte may include one or more of an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a polymer electrolyte, and a combination thereof.

[0065] The sulfide-based solid electrolyte is not particularly limited, and examples thereof may include Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is any one selected from Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and m is any one selected from P, Si, Ge, B, Al, Ga and In), Li 10 G 2 S 12 wait.

[0066] Examples of oxide-based solid electrolytes may include perovskite-type LLTO (Li 3x La 2 / 3-x TiO 3 ), phosphate-based NASICON-type LATP (Li 1+ x Al x Ti 2-x (PO 4 ) 3 )wait.

[0067] Examples of the polymer electrolyte may include a gel polymer electrolyte, a solid polymer electrolyte, and the like.

[0068] The solid electrolyte layer 30 may further include a binder. Examples of the binder may include butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), and the like.

[0069] The positive electrode active material layer 40 may include a positive electrode active material, a solid electrolyte, a conductive material, a binder, and the like.

[0070] The positive electrode active material can reversibly convert lithium ions (Li + ) embedding and de-embedding. The positive electrode active material may include an oxide active material. Examples of the oxide active material may include a rock-salt-layer-type active material, such as LiCoO 2 、LiMnO 2 、LiNiO 2 、LiVO 2 , Li 1+ x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 etc.; spinel-type active material, such as LiMn 2 O 4 、Li(Ni 0.5 Mn 1.5 ) 4 etc.; inverse-spinel-type active material, such as LiNiVO 4 、LiCoVO 4 etc.; olivine-type active material, such as LiFePO 4 、LiMnPO 4 、LiCoPO 4 、LiNiPO 4 etc.; silicon-containing active materials such as Li 2 FeSiO 4 , Li 2 MnSiO 4etc.; a rock salt layer-type active material in which part of the transition metal is replaced by a different metal, such as LiNi 0.8 Co (0.2-x) Al x O 2 (0 < x < 0.2); a spinel-type active material in which part of the transition metal is replaced by a different metal, such as Li 1+x Mn 2-x-y M y O 4 (where M is selected from Al, Mg, Co, Fe, Ni, and Zn, 0 < x + y < 2), lithium titanate such as Li 4 Ti 5 O 12 etc.

[0071] The solid electrolyte can be selected from oxide-based solid electrolytes, sulfide-based solid electrolytes, and polymer electrolytes and their combinations. The solid electrolyte included in the positive electrode active material layer 40 can be the same as or different from the solid electrolyte of the solid electrolyte layer 30.

[0072] There is no particular limitation on the sulfide-based solid electrolyte, and examples thereof may include Li 2 S-P 2 S 5 、Li 2 S-P 2 S 5 -LiI、Li 2 S-P 2 S 5 -LiCl、Li 2 S-P 2 S 5 -LiBr、Li 2 S-P 2 S 5 -Li 2 O、Li 2 S-P 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 、Li 2 S-SiS 2 -LiI、Li 2 S-SiS 2 -LiBr、Li 2 S-SiS 2 -LiCl、Li 2 S-SiS 2 -B 2 S 3 -LiI、Li 2 S-SiS 2-P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is any one selected from Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li x MO y (wherein x and y are positive numbers, and m is any one selected from P, Si, Ge, B, Al, Ga and In), Li 10 G 2 S 12 wait.

[0073] Examples of oxide-based solid electrolytes may include perovskite-type LLTO (Li 3x La 2 / 3-x TiO 3 ), phosphate-based NASICON-type LATP (Li 1+x Al x Ti 2-x (PO 4 ) 3 )wait.

[0074] Examples of the polymer electrolyte may include a gel polymer electrolyte, a solid polymer electrolyte, and the like.

[0075] Examples of the conductive material may include carbon black, conductive graphite, vinyl black, carbon fiber, graphene, and the like.

[0076] Examples of the binder may include butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), etc. The binder included in the positive active material layer 40 may be the same as or different from the binder in the solid electrolyte layer 30 .

[0077] The positive electrode current collector 50 may be a plate-shaped substrate having conductivity. Specifically, the positive electrode current collector 50 may be in the form of a sheet or a film.

[0078] The positive electrode current collector 50 may be one or more of indium, copper, magnesium, aluminum, stainless steel, iron, and combinations thereof.

[0079] A better understanding of the present invention can be obtained through the following examples. These examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.

[0080] Example 1

[0081] A half-cell with lithium metal as the counter electrode was fabricated as follows.

[0082] By adding about 90 mg of L 6 PS 5 Cl 0.5 Br 0.5 The powder was placed in a mold with an inner diameter of about 10 mm and pressed at about 200 MPa to form a solid electrolyte layer. The negative electrode layer was formed by placing magnesium powder on one side of the solid electrolyte layer and pressing it at about 380 MPa. A half-cell was made by attaching a lithium foil with a thickness of about 400 μm to the remaining side of the solid electrolyte layer.

[0083] Figure 4A is a TEM image showing magnesium powder. The average particle size (D50) of the magnesium powder was determined to be about 500 nm.

[0084] Figure 4B is a TEM image showing a cross-sectional view of the solid electrolyte layer and the negative electrode layer in a half-cell. The magnesium powder in the negative electrode layer maintains its particle shape. The thickness of the negative electrode layer is about 4.5 μm.

[0085] Comparative Example

[0086] A half cell was manufactured in the same manner as in Example 1, except that nickel (Ni) powder, which does not react with lithium and does not form an alloy, was used instead of magnesium powder.

[0087] The half-cell according to Example 1 was charged and discharged under the following conditions. Operating pressure: Use spring to apply constant pressure of about 5MPa Working temperature: about 30℃ Current: 0.5mA / cm 2 Capacity: 1mAh / cm 2 , 2mAh / cm 2 and 4mAh / cm 2

[0088] Figure 5A The half-cell according to Example 1 is shown in FIG.2 SEM image of the cross-section of the negative electrode layer during charging. Figure 5B The half-cell according to Example 1 is shown in FIG. 2 SEM image of the cross-section of the negative electrode layer during charging. Figure 5C The half-cell according to Example 1 is shown in FIG. 2 SEM image of the cross-sectional view of the negative electrode layer when the capacity is charged. Here, the thickness of the negative electrode layer increases with the increase of capacity. Specifically, when the capacity is 1 mAh / cm 2 When the negative electrode layer thickness is about 9 μm, the capacity is 2 mAh / cm 2 When the negative electrode layer thickness is about 15.5μm; when the capacity is 4mAh / cm 2 , the thickness of the negative electrode layer was about 26.4 μm. The initial thickness of the negative electrode layer was about 4.5 μm, indicating that during the charging of the all-solid-state battery according to Example 1, its thickness increased by at least about 5 times.

[0089] Figure 5D Energy dispersive spectroscopy (EDS) analysis and Figure 5A Results for the same cross-section in . Figure 5E The use of energy dispersive spectroscopy to analyze Figure 5B Results for the same cross-section in . Fig. 5F The use of energy dispersive spectroscopy to analyze Figure 5C Here, lithium metal is contained in a state where magnesium is uniformly dispersed in the negative electrode layer. FIG. 5D to FIG. 5F It can be seen that the inter-particle pores expand as the distance between magnesium particles increases, and lithium metal is also accommodated in the inter-particle pores.

[0090] Figure 6 is a TEM image showing particles removed from a charged negative electrode layer after 10 charge / discharge cycles of the half-cell according to Example 1. The particles maintained a spherical shape even after charge / discharge, and a lattice of an alloy of magnesium and lithium was observed.

[0091] Figure 7The results of X-ray diffraction analysis of the negative electrode layer of the half-cell according to Example 1 are shown. The results of the negative electrode layer in the initial state before charge / discharge (pristine), the negative electrode layer when charged once (1st deposition), the negative electrode layer when discharged once (1st stripping), the negative electrode layer when discharged 10 times (10th stripping), and the negative electrode layer when discharged 20 times (20th stripping) are shown. The alloy phase of magnesium and lithium includes a magnesium-rich (magnesium-rich) α phase and a lithium-rich (lithium-rich) β phase. As charge / discharge proceeds, the intensity of the peak caused by the magnesium-rich α phase (peaks at 2θ=32°±0.5°, 34°±0.5°, and 37°±0.5°) decreases, and the intensity of the peak caused by the lithium-rich β phase (peak at 2θ=36°±0.5°) increases. In short, even at the first charge, magnesium and lithium are alloyed to form particles, and thereafter the amount of the alloy of magnesium and lithium increases as charge / discharge proceeds.

[0092] Figure 8 Shown at 0.5mA / cm 2 and 1mAh / cm 2 The coulombic efficiency of the half-cells according to Example 1 and the comparative example during charge / discharge was measured under the conditions of . Fig. 9 Shown at 0.5mA / cm 2 and 2mAh / cm 2 The coulombic efficiency of the half-cells according to Example 1 and the comparative example during charge / discharge was measured under the conditions of Figure 8 and Fig. 9 Example 1 exhibited average Coulombic efficiencies of 98.26% and 97.97% and stable operation for 140 cycles and 100 cycles, respectively.

[0093] Fig.10 Shown at 0.5mA / cm 2 and 2mAh / cm 2 The voltage distribution in the first and second cycles when the half-cell according to Example 1 is charged / discharged under the conditions of . Example 1 exhibits a nucleation overpotential in the form of (√) in the first cycle, but exhibits an overpotential in the form of (L) from the second cycle onwards. This means that after the first cycle in which lithium nucleation is first performed, stabilization of lithium deposition is performed by alloying with magnesium.

[0094] Example 2

[0095] A full cell with lithium metal as the counter electrode was fabricated as follows.

[0096] By adding about 90 mg of L 6 PS5 Cl 0.5 Br 0.5 The powder was placed in a mold with an inner diameter of about 10 mm and rolled at about 200 MPa to form a solid electrolyte layer. The negative electrode layer was formed by placing magnesium powder on one side of the solid electrolyte layer and rolling it at about 380 MPa. The positive electrode active material layer was formed by placing 20 mg of a mixed powder including a positive electrode active material, a solid electrolyte and a conductive material on the remaining side of the solid electrolyte layer and rolling it at about 380 MPa. The positive electrode active material used was coated with LiNbO 2 NCM 811, the solid electrolyte used is L 6 PS 5 Cl 0.5 Br 0.5 , the conductive material used was SC65 carbon. The mixed powder was prepared by adding 3 parts by weight of the conductive material to 100 parts by weight of a powder mixture including a positive electrode active material and a solid electrolyte in a mass ratio of 7:3.

[0097] The full battery according to Example 2 was charged and discharged under the following conditions. Operating pressure: Use a cell operation kit to apply a constant pressure of about 30MPa Working temperature: about 30℃ Current and capacity: 0.5mA / cm 2 , cut-off voltage is 3V-4.3V

[0098] Fig.11 A graph showing the cycle capacity and cycle coulombic efficiency of the full battery according to Example 2 is shown. Referring to this, Example 2 exhibits stable operation over 190 cycles. In particular, Example 2 exhibits a high capacity retention rate of about 86.1% in 180 cycles except for the initial 10 cycles in which the irreversible effect is large, and exhibits a high average coulombic efficiency of about 99.92% during lithium insertion / deinsertion into / from the negative electrode layer except for the initial 10 cycles.

[0099] As is apparent from the above description, according to the present invention, an all-solid-state battery including a negative electrode layer capable of accommodating a large amount of lithium metal during charging can be obtained.

[0100] According to the present invention, an all-solid-state battery with high coulombic efficiency and long life can be obtained.

[0101] The effects of the present invention are not limited to the above-mentioned effects. It should be understood that the effects of the present invention include all effects that can be inferred from the description of the present invention.

[0102] The test examples and implementation schemes of the present invention are described in detail above, but the scope of the present invention is not limited to the above test examples and implementation schemes. Various modifications and improvements made by technicians in this field using the basic concepts of the present invention defined in the attached claims are also within the scope of the present invention.

Claims

1. An all-solid-state battery, comprising: Anode current collector; A negative electrode layer, the negative electrode layer is disposed on the negative electrode current collector; A solid electrolyte layer, wherein the solid electrolyte layer is disposed on the negative electrode layer; a positive electrode active material layer, the positive electrode active material layer being disposed on the solid electrolyte layer; and a positive electrode current collector, the positive electrode current collector being disposed on the positive electrode active material layer, The negative electrode layer includes (i) particles and (ii) inter-particle pores, wherein the particles include a metal capable of alloying with lithium.

2. The all-solid-state battery according to claim 1, wherein the metal comprises at least one of magnesium (Mg), silver (Ag), zinc (Zn), bismuth (Bi), tin (Sn), or a combination thereof.

3. The all-solid-state battery according to claim 1, wherein: The average particle size (D50) of the particles is 300nm-700nm. 4 . The all-solid-state battery according to claim 1 , wherein in the negative electrode layer, the particles are configured to maintain a spherical shape or an elliptical shape. The all-solid-state battery according to claim 1 , wherein the negative electrode layer is formed only of the particles. The all-solid-state battery according to claim 1 , wherein the particles further comprise an alloy of the metal and lithium.

7. The all-solid-state battery according to claim 1, wherein: During charging of the all-solid-state battery, lithium metal is accommodated in the inter-particle pores.

8. The all-solid-state battery according to claim 1, wherein alloying between the particles and lithium occurs during charging of the all-solid-state battery.

9. The all-solid-state battery according to claim 1, wherein: During charging of the all-solid-state battery, lithium metal is deposited on the surface of the particles, thereby (i) increasing the distance between the particles, (ii) enlarging the inter-particle pores, and (iii) accommodating the lithium metal in the inter-particle pores.

10. The all-solid-state battery according to claim 1, wherein: The negative electrode layer satisfies the following formula 1: [Formula 1] 2≤T2 / T1≤5.9 Wherein, T1 is the thickness of the negative electrode layer when the all-solid-state battery is fully discharged, and T2 is the thickness of the negative electrode layer when the all-solid-state battery is fully charged.

11. The all-solid-state battery according to claim 1, wherein: Based on the X-ray diffraction analysis of the negative electrode layer, the peak intensities at 2θ=32°±0.5°, 34°±0.5°, and 37°±0.5° decreased as charge and discharge progressed.

12. The all-solid-state battery according to claim 1, wherein: Based on the X-ray diffraction analysis of the negative electrode layer, the peak intensity at 2θ=36°±0.5° increases as charge and discharge proceed.

13. A method for operating an all-solid-state battery according to claim 1, comprising performing charging and discharging at 25°C-45°C.